PUBLIC STIGMA TERHADAP ORANG DENGAN GANGGUAN JIWA DI KABUPATEN KEBUMEN - Asti, Arnika Dwi; Sarifudin, Sahrul; Agustin, Ike Mardiati (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
Indonesian Basic Health Research Data (2013) showed that the prevalence of people with mental disorders in Central Java is 3.3% of the entire population and Kebumen district ranked as the second region with 773 people were detected as mental disorders in 2012. People with mental disorders experienced self stigma and also public stigma from the community in the form of labels, prejudice and discrimination (Corrigan, 2005). The purpose of this study is to describe the public stigma given by the community to the people with mental disorders in Kebumen district.            This was a quantitative study with descriptive analytic method and survey approach, conducted in March 2016 in Rogodono village, Buayan, Kebumen district. The sample were 207 people taken by proportional random sampling technique. The study used demographic characteristics questionnaire and ODGJ public stigma questionnaire that modified from the Perceived Stigma of Substance Abuse Scale (PSAS) questionnaire by Luoma (2010). The data analysis used univariate descriptive.            The results show that most of the respondents were female (59.4%), with an age range 41-50 years (32.4%), elementary education (49.3%), working as laborers (47.8%) and provide public stigma of prejudice (87.43%). Public stigma effect on healing and the incidence of recurrence clients with mental disorders in the community. It is important for nurses to do health promotion and education in order to improve the cure rate and lower the recurrence rate clients with mental disorders in the community Keywords: Descriptive Analytical, Mental Disorder, Public Stigma